Doctor, something is stuck in my eye! - Erika Poggiali; Alessandro Dacrema; Andrea Vercelli (Emergency Care Journal)
A 62-year-old Italian woman presented to our emergency room with complaints of redness and a foreign body sensation in her left eye since the day before. Her vision was unaffected, and she she felt well otherwise. She had no previous history of similar episodes, ocular trauma, or foreign body incidents, and there was no record of any systemic illnesses or recent travel. She lived with her pet dog. Laboratory tests, including C-reactive protein and eosinophil count, resulted all normal. On ocular examination, her visual acuity was 20/20 in both eyes. Diffuse conjunctival congestion was noted in the left eye and a large live nematode was visualized in the temporal part of the bulb under the conjunctiva (Video 1). The cornea anterior chamber and the fundus examination were unremarkable.